Structural Characterization and Immunomodulatory Activity of an Exopolysaccharide Produced by Probiotic Leuconostoc mesenteroides 201607 Isolated from Fermented Food - Selvakumar Vijayalakshmi; Jong-Rai Kim; Ramachandran Chelliah; Kaliyan Barathikannan; Abdurahman Hajinur Hirad; Deog-Hwan Oh (Applied Microbiology, 2024)
Fermented foods containing probiotic Leuconostoc mesenteroides 201607 (LM) were used to extract exopolysaccharides. An incomplete understanding exists regarding the immunomodulatory characteristics of exopolysaccharides (EPSs), which are important constituents of bacterial biofilms. In this instance, we examined the immunomodulatory capacity of EPSs from fermented food extracted from L. mesenteroides 201607. Partially purified exopolysaccharide from L. mesenteroides 201607 (PP-LMEPS) consists of glucose (57.1%), rhamnose (29.53%), and galactose (13.36%). The maximum EPS yield was attained after 30 h of incubation at 37 °C and an initial pH of 7.0. When lipopolysaccharide-stimulated RAW264.7 was exposed to PP-LMEPS, the inflammatory cytokines were considerably decreased or elevated dose-dependently. Upon the exposure of lipopolysaccharide-stimulated RAW264.7 cells to PP-LMEPS, a dose-dependent modulation of inflammatory cytokines was observed. This suggests that the extracted EPS possesses immunomodulatory characteristics, as evidenced by a significant decrease or increase in inflammatory cytokine levels. However, further research is warranted to fully elucidate the precise mechanisms and potential therapeutic implications of the immunomodulatory properties of PP-LMEPS.